Work Readiness of Competencies Machining Engineering’s Student - Nur Aini Susanti; Suparji Suparji; Tri Wrahatnolo; Hanna Zakiyya; Yuli Sutoto Nugroho (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Vocational High School or Sekolah Menengah Kejuruan (VHS) is one of the levels of education in Indonesia. VHS provides various skills programs. VHS graduates should have more significant opportunities to work based on their competencies, but the most dominant unemployed were VHS graduates in East Java, Indonesia. VHS’s students must have work readiness and vocational competencies to reduce unemployment. The mechanical Engineering program encourages students to operate machines and produce goods. Machine CNC is one of the manufacturing industries. The research aims to analyze the influence of problem-solving, technology, teamwork, and self-management skills on the work readiness of VHS students in the Mechanical Engineering program. Method: This research used quantitative methods with a causality approach. The population was students of the Mechanical Engineering program in East Java Province in Indonesia. The random sampling technique was used with 377 respondents. Analysis data used SEM. Results: Problem-solving skills were 36.7% influenced by technology, teamwork, and self-management. Work readiness was 54.6% influenced by problem-solving skills. Novelty: The significant positive influence of problem-solving skills, technology skills, teamwork skills, and self-management skills on the work readiness of students at Machining Engineering Vocational High School in East Java simultaneously.